Structured or emotion? Teacher and student perceptions of genre-based vs. multisensory pedagogies in EFL writing classrooms - Baehaqi, Luqman; Lian, Ania; Sudimantara, Lala Bumela; Miftah, M. Zaini (Journal of Research on English and Language Learning (J-REaLL), 2025)
This study explores the effectiveness of two pedagogical approaches—genre-based (grounded in systemic functional linguistics, SFL) and multisensory instruction—in Indonesian EFL teacher education. While the genre-based approach emphasizes structured textual analysis and explicit feedback, the multisensory method integrates auditory, visual, and emotional modalities to enhance engagement. Through qualitative phenomenological analysis, including interviews and reflective journals from six students and two lecturers, the study examines perceptions of support, engagement, and skill development. Findings reveal that the genre-based approach improved grammatical precision and reduced reliance on translation tools but often led to passive learning and limited metacognitive awareness. Conversely, the multisensory approach fostered emotional-text connections and autonomous learning through techniques like the reading for emotion method (REM) and verbotonal exercises, though repetitive tasks occasionally caused fatigue. Lecturers noted that while SFL strengthened structural competence, it struggled to cultivate creativity, whereas multisensory methods enhanced engagement but required a better balance between autonomy and guidance. Theoretical implications highlight the value of integrating neuroscientific principles with sociocultural learning theories to optimize writing instruction. The study advocates for a hybrid model that combines the scaffolding benefits of genre-based pedagogy with the motivational and cognitive advantages of multisensory techniques. Recommendations include diversifying tasks to sustain engagement, reducing over-reliance on translation tools, and fostering metacognitive reflection. Future research should investigate longitudinal impacts and ideal sensory-structural balances to enhance EFL writing instruction in similar contexts.